Investigating Memory Updating in Mice Using the Objects in Updated Locations Task. Issue 1 (27th January 2020) - Wright, Destiny S.; Bodinayake, Kasuni K.; Kwapis, Janine L.
Abstract: In the laboratory, memory is typically studied as a de novo experience, in which a naïve animal is exposed to a discrete learning event that is markedly different from its past experiences. Most real‐world memories, however, are updates—modifications or additions—to existing memories. This is particularly true in the aging, experienced brain. To better understand memory updating, we have developed a new behavioral paradigm called the objects in updated locations (OUL) task. OUL relies on hippocampus‐dependent spatial learning and has the advantage of being able to test both the original memory and the updated information in a single test session. Further, OUL relies on incidental learning that avoids unnecessary stress that might hinder the performance of aging animals. In OUL, animals first learn the location of two identical objects in a familiar context. This memory is then updated by moving one object to a new location. Finally, to assess the animals' memory for the original and the updated information, all animals are given a test session in which they are exposed to four copies of the object: two in the original training locations, one in the updated location, and one in a novel location. By comparing exploration of the novel location to the familiar locations, we can infer whether the animal remembers the original and updated object locations. OUL is a simple but powerful task that could provide new insights into the cellular, circuit‐level, and molecular mechanisms that support memory updating. © 2020 by John Wiley & Sons, Inc.